2020
DOI: 10.1002/lio2.481
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time feedback control of voice in cochlear implant recipients

Abstract: Objectives: To evaluate feedback-dependent vocal control in cochlear implant patients using pitch-shifted auditory feedback. Methods: Twenty-three CI recipients with at least 6 months of implant experience were enrolled. Vocal recordings were performed while subjects repeated the vowel /e/ and vocal signals were altered in real-time using a digital effects processor to introduce a pitch-shift, presented back to subjects using headphones. Recordings were analyzed to determine pitch changes following the pitch-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
(98 reference statements)
1
4
0
Order By: Relevance
“…This wide individual variability in speech adaptation behavior is not uncommon and has been reported by many other studies (Parrell and Niziolek, 2021;Martin et al, 2018;Munhall et al, 2009;Parrell et al, 2017;Villacorta et al, 2007). This variability was also reported in CI participants in f 0 control (Gautam et al, 2020). At the individual level, some CI participants showed even more speech adaptation behavior than some TH participants.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This wide individual variability in speech adaptation behavior is not uncommon and has been reported by many other studies (Parrell and Niziolek, 2021;Martin et al, 2018;Munhall et al, 2009;Parrell et al, 2017;Villacorta et al, 2007). This variability was also reported in CI participants in f 0 control (Gautam et al, 2020). At the individual level, some CI participants showed even more speech adaptation behavior than some TH participants.…”
Section: Discussionsupporting
confidence: 81%
“…The phoneme contrast in CI users' speech also improves over time with longer exposure to auditory feedback: significant improvement after just one month post-implantation, and more after one year post-implantation as compared to the pre-implantation status (Ménard et al, 2007). Additionally, similar to TH individuals, CI users also rely on auditory feedback in ongoing speech, producing more errors and speaking at a slower speech rate under conditions of a feedback delay (Taitelbaum-Swead et al, 2019), and changing the pitch of their voice in response to a shift in the fundamental frequency of their auditory feedback (Loucks et al, 2015;Gautam et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Recent results have suggested that implant recipients, for example, do have some ability to monitor and their auditory feedback, but that these abilities lack the fine control seen in normal individuals. 9 Additionally, dysfunction of vocal selfmonitoring and resulting feedback-dependent vocal control has also been seen in a variety of primary vocal disorders and neurologic disorders with vocal symptoms, including spasmodic dysphonia, 10 vocal cord paralysis, 11 Parkinson's disease, 12 and cerebellar degeneration. 13 A better understanding of the underlying neural and behavioral mechanisms may lead to better diagnostic and rehabilitation tools to improve patient communication deficits.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, although hearing restoration, including cochlear implants, improves vocal control and clarity of speech production, the communication abilities of these patients still lag behind those of normal hearing individuals 8 . Recent results have suggested that implant recipients, for example, do have some ability to monitor and their auditory feedback, but that these abilities lack the fine control seen in normal individuals 9 . Additionally, dysfunction of vocal self‐monitoring and resulting feedback‐dependent vocal control has also been seen in a variety of primary vocal disorders and neurologic disorders with vocal symptoms, including spasmodic dysphonia, 10 vocal cord paralysis, 11 Parkinson's disease, 12 and cerebellar degeneration 13 .…”
Section: Introductionmentioning
confidence: 99%